Combining hyperspectral imaging and chemometrics to assess and interpret the effects of environmental stressors on zebrafish eye images at tissue level. Issue 3 (4th October 2017) - Olmos, Víctor; Marro, Mònica; Loza‐Alvarez, Pablo; Raldúa, Demetrio; Prats, Eva; Padrós, Francesc; Piña, Benjamin; Tauler, Romà; de Juan, Anna
Abstract : Changes on an organism by the exposure to environmental stressors may be characterized by hyperspectral images (HSI), which preserve the morphology of biological samples, and suitable chemometric tools. The approach proposed allows assessing and interpreting the effect of contaminant exposure on heterogeneous biological samples monitored by HSI at specific tissue levels. In this work, the model example used consists of the study of the effect of the exposure of chlorpyrifos‐oxon on zebrafish tissues. To assess this effect, unmixing of the biological sample images followed by tissue‐specific classification models based on the unmixed spectral signatures is proposed. Unmixing and classification are performed by multivariate curve resolution‐alternating least squares (MCR‐ALS) and partial least squares‐discriminant analysis (PLS‐DA), respectively. Crucial aspects of the approach are: (1) the simultaneous MCR‐ALS analysis of all images from 1 population to take into account biological variability and provide reliable tissue spectral signatures, and (2) the use of resolved spectral signatures from control and exposed populations obtained from resampling of pixel subsets analyzed by MCR‐ALS multiset analysis as information for the tissue‐specific PLS‐DA classification models. Classification results diagnose the presence of a significant effect and identify the spectral regions at a tissue level responsible for the biological change. Abstract : Data analysis strategy to assess effects of environmental stressors on zebrafish eye images at tissue level.